Research of enhanced base strain on landslide-prone slopes under anthropogenic impact - Петренко, Єдуард Юрійович; Мохаммад, Махді Гараханлу (Eastern-European Journal of Enterprise Technologies, 2015)
Design and construction in landslide-prone areas are associated with both ensuring the soil mass stability and evaluating possible appearance and enhancement of the natural and anthropogenic factors. Finite element method is the most rational solution for this class of problems. Further development of computational methods is associated with the expansion of using the mathematical analogs of ground models based on numerical calculation methods. For such problems, a model that allows to consider natural conditions and variable anthropogenic factors in landslide-prone areas, taking into account the plastic deformation of soils within the "slope-retaining structure-building" system was proposed. The paper deals with the stress-strain state of the landslide-prone slope and influence of anthropogenic factors on the process. The simulation was performed using the SATER.SOIL software package. The results have allowed to determine the areas of plastic deformation of the soil, which allowed to estimate the degree of approximation to the ultimate stress state along the slope at all stages of loading, taking into account natural and anthropogenic factors. The change in the stress-strain state of the soil mass using various engineering protection structures and their effectiveness within the "slope-retaining structure-building" system was considered.